Highly enhanced field emission from CuO nanowire arrays by coating of carbon nanotube network films. (May 2015) - Hu, Hailong; Zhang, Dian; Liu, Yuhui; Yu, Weiming; Guo, Tailiang
Abstract: Vertically aligned CuO nanowires are coated with CNT network films to achieve a significant improvement in field electron emission. The turn-on field of CuO nanowire array cathodes is decreased from 6.6 V/μm to below 1.2 V/μm owing to the CNT film coating. Compared to the needle-like CuO structures that could perforate the CNT film coating, CuO nanowires with uniform diameter are more suitable to be wrapped by CNT network films from top to bottom. It is found that the coverage of CNTs over CuO nanowire surface plays a role in affecting the turn-on fields and emission stabilities. Highlights: CNT-wrapped CuO nanowire arrays were prepared via wet chemical process. CuO nanowires with uniform diameter were in favor of a whole CNT-wrapping. The turn-on field of CuO nanowire cathode decreased from 6.6 V/μm to below 1.2 V/μm. Decreasing the CNT coverage could enhance the stability of emission current.